2016
DOI: 10.1371/journal.ppat.1005641
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Targeted Nipah Virus Glycoproteins Improve Cell-Type Selective Gene Delivery and Reveal a Preference for Membrane-Proximal Cell Attachment

Abstract: Receptor-targeted lentiviral vectors (LVs) can be an effective tool for selective transfer of genes into distinct cell types of choice. Moreover, they can be used to determine the molecular properties that cell surface proteins must fulfill to act as receptors for viral glycoproteins. Here we show that LVs pseudotyped with receptor-targeted Nipah virus (NiV) glycoproteins effectively enter into cells when they use cell surface proteins as receptors that bring them closely enough to the cell membrane (less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 64 publications
1
97
0
Order By: Relevance
“…NiV-LVs retargeted to EpCAM, CD8, CD117, or GluA4 were used successfully. 93 These reports demonstrate that in the recent years, largely due to the tremendous flexibility of paramyxoviral envelopes, targeting of LVs to specific cell types has become more feasible and efficient.…”
Section: Targeted Pseudotypingmentioning
confidence: 99%
“…NiV-LVs retargeted to EpCAM, CD8, CD117, or GluA4 were used successfully. 93 These reports demonstrate that in the recent years, largely due to the tremendous flexibility of paramyxoviral envelopes, targeting of LVs to specific cell types has become more feasible and efficient.…”
Section: Targeted Pseudotypingmentioning
confidence: 99%
“…Although this could be very efficient for ex vivo B cell transduction, this vector lacks selectivity for B cells, making direct in vivo application difficult. A recent paper demonstrated that the Nipah virus (NiV) glycoproteins can be engineered for receptor targeting of LV, resulting in substantially improved vector production yields, while retaining the high selectivity of the MV-based system 39 . In particular, when the same CD20-specific scFv that was used here on the MV glycoproteins was used on the NiV glycoproteins, vector production yields increased by more than two orders of magnitude, making a scale-up for the production of clinical vector lots conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NiV glycoproteins appear to be a more appropriate option for generating the pseudotyped LVs than MV or TPMV. However, the pseudotyped NiV‐LVs are highly sensitive to the position of the binding site to the target receptor and proximal positions of the membrane are preferred to the membrane distal, which may slightly limit their use …”
Section: Introductionmentioning
confidence: 99%
“…However, the pseudotyped NiV-LVs are highly sensitive to the position of the binding site to the target receptor and proximal positions of the membrane are preferred to the membrane distal, which may slightly limit their use. 27 Given the above explanations, we aimed to design a novel Figure 1A and B), using the lipofectamine reagent (Thermo Fisher Scientific, Waltham, MA, USA) as described previously. 29 The Figure 1B).…”
Section: Introductionmentioning
confidence: 99%